Food, farming and religion: emerging ethical perspectives - Van Wieren, Gretel (Routledge environmental humanities, 2018)
Down on the farm : the historical roots of the ecological crisis : agriculture? -- Soil : sacred and profaned -- Plants : the power and miracle of seeds -- Animals : humane, sustainable, spiritual meat? -- Water : precious, polluted, purified -- Climate : religion and food for a hot planet -- The new sacred farm